Teaching Social Sciences: Intermediate and senior phases (Oxford University Press, 180 pp. ISBN 978 0 19 042145 8) Johan Wassermann (Ed.) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The book titled Teaching Social Sciences: Intermediate and senior phases is a great compilation comprising six chapters that engages with issues concerning the teaching of Social Sciences in the intermediate and senior phases. The six chapters deal with issues like the history of social sciences, the need for teaching History and Geography, using an Ubuntu-based pedagogy and integrating ICT when teaching Social Sciences.
Keywords: teaching; Social Sciences; intermediate phases; senior phases; Ubuntu-based pedagogy; ICT